Accounting, a love language - Rafles Ginting; Eirene Maharani Putri Purba; Auriel Ladisma Ragasiwi; Khristina Yunita (FORUM EKONOMI, 2023)
Accounting has an important role in married life, many millennial couples who are not married yet are also interested and need to manage finances. They cannot control their financial management properly so they tend to spend their money and have no mutual savings for the future. Mental accounting will be easy to apply if financial management is carried out in a disciplined manner. Therefore, the authors wanted to examine how accounting helps couples to know their income and expenses so far by budgeting, recording, decision-making, and long-term financial planning for managing their finances. This paper aims to elaborate on accounting with a different meaning, not accounting in the business field but in the family. To obtain the answer to the research questions, therefore qualitative method was used followed by the use of an interpretive paradigm. Based on the findings of this research, accounting is needed to achieve the household financial goals both short and long-term. Accounting in the household is a benchmark for partners to understand to avoid the 'fear' of failure in marriage.